Post-contractual non-compete clause in commercial agency contracts - Kerčmar, Sebastjan (Lexonomica, 2025)
This paper deals with the legal regime governing post-contractual non-compete clauses in commercial agency contracts, analysing Slovenian legislation and its compliance with Directive86/653/EEC. The Slovenian Obligations Code (OZ) requires the mandatory payment of compensation for compliance with a non-compete clause only in cases where the contract is terminated for reasons attributable to the principal. The author stresses that such a regime may lead to a restriction of contractual freedom without adequate compensation, which is not in line with the spirit of the Directive. Based on a review of the regimes inrespect of non-compete clauses after the termination of a commercial agency contract in various European countries, including Croatia, the author finds that the regimes vary considerably between countries. The paper also focuses on the impact of non-compete clauses on indemnity, as the OZ requires such clauses to be taken into consideration in determining the amount. The author draws attention to the need for a fair balance of interests and for legislation to be revised to ensure that agents are protected against disproportionate restrictions without adequate compensation.
Keywords: commercial agent; commission; Directive 86/653/EEC; indemnity; monthly compensation for post-contractual non-compete clause; post-contractual non-compete clause